2018
DOI: 10.1016/j.ijdevneu.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cerebral ventricular volumes and cortical thicknesses in normal rats and Genetic Absence Epilepsy (GAERS): A developmental study

Abstract: Ventricular enlargement and cortical atrophy have been associated with various central nervous system diseases. The aim of the present study was to measure the volumes of the lateral (LV) and third (3V) ventricles and to determine the cortical thickness for the motor (MCx), somatosensory (SSCx), visual (VCx) and auditory (AuCx) cortex and the striatum of Wistar rats, in a developmental series at 10, 20, 30, and 60 days postnatal, and to compare them with similar data from genetic absence epilepsy rats from Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Boullieret et al ( 81 ) also found increased volumes in GAERS compared to NEC in amygdala and cortex already at 3 months of age. But, Kirazli et al ( 82 ) reported reduced thickness in auditory and visual cortices, and striatum, and overall brain size in GAERS at 1 and 2 months of age based on a histological study. Notably, in that study, normal Wistar and GAERS did not show significant volumetric differences at P10, and the authors speculated that GAERS are ordinary at that early age.…”
Section: Discussionmentioning
confidence: 99%
“…Boullieret et al ( 81 ) also found increased volumes in GAERS compared to NEC in amygdala and cortex already at 3 months of age. But, Kirazli et al ( 82 ) reported reduced thickness in auditory and visual cortices, and striatum, and overall brain size in GAERS at 1 and 2 months of age based on a histological study. Notably, in that study, normal Wistar and GAERS did not show significant volumetric differences at P10, and the authors speculated that GAERS are ordinary at that early age.…”
Section: Discussionmentioning
confidence: 99%
“…As a measurement of brain development, cortical thickness was measured quantified from Nissl-stained tissue sections of neonatal brains at P5 (Figure 6B). 27 Compared with those from ZIKV-infected dams, neonatal brains from sEVs RVG -siRNA treated dams had normal cortical thickness (Figure 6C). This was supported by studies that showed when inflammation or infection occurred in the brain, Iba1 + microglia were activated and acquired phagocytic ability, and accompanied by the amebic morphology.…”
Section: Optimization Of Loading Efficiency Of Sevs Rvg With Zikv-specific Sirnas and Inhibition Of Zikv Replication In Vitromentioning
confidence: 91%